Re‐Evaluating Historical Sea Surface Temperature Data Sets: Insights From the Diurnal Cycle, Coral Proxy Data, and Radiative Forcing - Duo Chan; Geoffrey Gebbie; Peter Huybers (Geophysical Research Letters, 2025)
Abstract Discrepancies in historical global mean surface temperature (GMST) estimates largely stem from differences in bias corrections applied to sea surface temperature (SST) records. Here, using the amplitude of the diurnal cycle in SST, we provide evidence that wooden‐to‐canvas bucket transitions were mostly complete by the early 1900s, earlier than commonly assumed by two decades, resulting in strong early 20th century cold biases. We then use this diurnal evidence, together with coral δ18O and Sr/Ca proxies and expected GMST responses to external radiative forcing, to evaluate four different SST estimates: HadSST4, ERSST5, COBESST2, and DCSST. Of these, DCSST, developed by our team through adjustment of SSTs to match coastal land surface air temperatures, shows the closest overall agreement with all three lines of evidence. DCSST features a larger and steadier warming since the 1900s relative to the other estimates and indicates somewhat higher transient climate sensitivity and smaller decadal variability.